Mechanical Circulatory Support of the Fontan Patient - Woods, Ronald K.; Ghanayem, Nancy S.; Mitchell, Michael E.; Kindel, Steven; Niebler, Robert A. (Seminars in thoracic and cardiovascular surgery. Pediatric cardiac surgery annual, 2017)
Because of the inadequacies inherent to a circulation supported by a single ventricle, many Fontan patients will experience failure of their circulation. To date, there is no medical regimen that reliably and consistently restores circulatory function in these patients. Because of the shortage of donor organs and the fact that many of these patients present with features that either preclude or render heart transplantation a high risk, there is an intense need to better understand how mechanical circulatory support (MCS) may benefit these patients. In this report, we share our experience of successful MCS and transplantation of three patients. Our experience and that of others is very encouraging, but also preliminary. In general, a systemic ventricular assist device, with or without a Fontan fenestration, is a reasonable consideration for a patient presenting with predominantly systolic dysfunction. A pulmonary/systemic venous assist device may be sufficient for the patient with preserved systolic function and failure of the systemic venous/lymphatic system; however, this remains speculative. The more comprehensive approach of a total artificial heart or bilateral support is attractive in theory, but beset by the need for a more complex operation. In all scenarios, early referral, before organ failure, is paramount to successful MCS.